Eleventh Five Year Plan (2007-2012) Volume-III Agriculture, Industry, Services and Physical Infrastructure - Planning Commission (Planning Commission, 2007)
Growth of agricultural GDP decelerated from over 35% per year during 1981/82-1996/97 to only around 2% during 1997/98-2004/05 (see Table 1.4). This deceleration, although most marked in rain-fed areas, occurred in almost all States and covered almost all major sub-sectors, including those such as horticulture, livestock and fisheries where growth was expected to be high (see Table 1.3).
Government of India
Government of India